Lipase production by Aspergillus niger 11T53A14 in wheat bran using experimental design methodology. - SANTOS, R. R. dos (2014)
Lipases have various industrial applications and their production by filamentous fungi in solid state fermentation (SSF) process is of interest. In this work the lipase enzyme production by the mutant Aspergillus niger 11T51A14, which is a well-known lipase producer was studied using wheat bran as substrate. Microorganism used in fermentation process was inoculated at a concentration of 107 spores/gm into the medium containing nitrogen (ammonium sulfate), sunflower soapstock and wheat bran. The SSF process for enzyme production was carried out in aerated columns immersed in a water bath at 32ºC for 72 h. The process was studied using a central composite rotatable design 22, where variables tested were the nitrogen concentration (0.32-0.88 % w/w) and the volume of liquid (60.9-89.1 mL). The lipase activity was analyzed in enzymatic extracts. The wheat bran, in the fermentation medium, acted as a carbohydrate source and as an inducer for the lipase production. The maximum enzyme activity found was 153.4 U/gdm, with a nitrogen concentration of 0.6 % and 89.1 mL of volume of liquid. The response surface model demonstrated that higher volume of liquid had a positive effect in lipase activity, while nitrogen concentration showed an optimal range (0.4-0.6%).